Atribuições causais e rendimento escolar: Impacto das habilitações escolares dos pais e do género dos alunos - Suely Mascarenhas; Leandro S. Almeida; Alfonso Barca (Universidade do Minho, 2005)
This paper analyses the relationship between causal attributions and academic achievement, considering attributions by students parents, school level, and gender. To evaluate causal attributions we use the scale "Avaliação das Atribuições Causais e Multidimensionais" (Barca, 2000) and a sample of 1144 students from basic public and private schools of Randonia State (Amazônia, Brazil). Results suggest that, students causal attributions are not differentiated by school achievement. Most students use internal attributions (capacities and effort) to explain their good schools marks, using external attributions (luck or teachers) to explain bad school classifications. Even tough, poorest achievement students justify, in large percentage, better marks by luck and facility of examinations, as well as low capacity to explain low school classifications. The causal attributions are not related to students´ gender, but male students from parents with low academic certifications tend to justify low school marks by lack of capacity. Finally, to justify good and bad marks by effort, or lack of effort, is more frequent in the students from parents with high school levels.